Resourcing, annotating, and analysing synthetic peptides of SARS‐CoV‐2 for immunopeptidomics and other immunological studies. Issue 17 (14th April 2021) - Li, Chen; Revote, Jerico; Ramarathinam, Sri H.; Chung, Shan Zou; Croft, Nathan P.; Scull, Katherine E.; Huang, Ziyi; Ayala, Rochelle; Braun, Asolina; Mifsud, Nicole A.; Illing, Patricia T.; Faridi, Pouya; et al.
Abstract: SARS‐CoV‐2 has caused a significant ongoing pandemic worldwide. A number of studies have examined the T cell mediated immune responses against SARS‐CoV‐2, identifying potential T cell epitopes derived from the SARS‐CoV‐2 proteome. Such studies will aid in identifying targets for vaccination and immune monitoring. In this study, we applied tandem mass spectrometry and proteomic techniques to a library of ∼40, 000 synthetic peptides, in order to generate a large dataset of SARS‐CoV‐2 derived peptide MS/MS spectra. On this basis, we built an online knowledgebase, termed virusMS (https://virusms.erc.monash.edu/ ), to document, annotate and analyse these synthetic peptides and their spectral information. VirusMS incorporates a user‐friendly interface to facilitate searching, browsing and downloading the database content. Detailed annotations of the peptides, including experimental information, peptide modifications, predicted peptide‐HLA (human leukocyte antigen) binding affinities, and peptide MS/MS spectral data, are provided in virusMS.